A formação de professores em uma pós-graduação lato sensu para a atuação no atendimento educacional especializado - Ataide, Janaina Correia Vidal (2021)
The Special Education in the perspective of Inclusive Education goes through a challenging path, especially in Brazil, specifically in Paraíba. The dissertation that follows, came from the concerns about the challenges faced by the teacher of Specialized Education Care in their performance in everyday school, questioning their professional training. It has as a general objective to analyze the formation of teachers in a sensu lato post-graduation course to act in the Specialized Educational Attendance and, as specific objectives: analyze the curricular structure of a sensu lato post-graduation course in Specialized Educational Attendance; identify the perceptions of the teachers and graduates about the formation in a sensu lato post-graduation course to act in the Specialized Educational Attendance; and identify the graduates' perceptions about the performance of the Specialized Educational Attendance teacher in the teaching-learning process of students who are Special Education targets. For the theoretical foundation, we sought authors who discuss about the specialized educational care, continuing education and the curriculum, in addition to the support of current legislation for the entire educational process of the country and the state where the research is located and, specifically, the legislation around Special Education from the perspective of Inclusive Education. To develop the research, the methodological basis was the case study. Initially, a document analysis of the pedagogical project of the course was carried out, in order to meet the dissertation's objective. Afterwards, a semi-structured interview was carried out with course graduates and teacher trainers, by means of a script previously presented to the judges with knowledge in the area of Special Education, who were able to contribute to its construction. Categories and subcategories were established and the analyses proceeded, which resulted in the fact that the graduates realize the importance of the specialized educational service teacher's role for the development of the teaching-learning process of the students who are the target of Special Education and that the continued education had its positive aspects in the perception of the graduates and the teacher trainers, the lato sensu level teacher training in Specialized Educational Attendance needs updating of the curriculum so that it can better meet the daily demands of the Specialized Educational Attendance professional's work with target students of Special Education in the regular education system.